Metabolic and immunological evaluation of patients with indeterminate and cardiac forms of Chagas disease. Issue 51 (18th December 2020) - Rocha, Ivonete Helena; Ferreira Marques, Ana Luisa; Moraes, Giselle Vanessa; Alves da Silva, Djalma Alexandre; Silva, Marcos Vinicius da; Rodrigues, Virmondes; Cunha, Daniel Ferreira da; Correia, Dalmo
Abstract : Abstract: Chagas disease affects approximately 7 million people, causing disability and mortality in the most productive life stages of infected individuals. Considering the lifestyle of the world population, metabolic syndrome is a synergistic factor for an increased cardiovascular risk of patients with Chagas disease. This study transversally evaluated the metabolic and immunological profiles of patients with indeterminate (IF) and cardiac (CF) forms of Chagas disease and their correlations with left ventricular dysfunction (LVD). Clinical and electrical bioimpedance analysis, levels of cytokines (interferon [IFN]-γ, tumor necrosis factor [TNF]-α, interleukin [IL]-17, IL-10, and IL-33) and adipocytokines (adiponectin, leptin, and resistin), metabolic syndrome components, and brain natriuretic peptide (BNP) levels were assessed in 57 patients (13 IF and 44 CF) with a mean age of 61.63 ± 12.1 years. Chest x-ray, electrocardiogram, and echocardiogram were performed to classify the clinical forms. The CF group had a higher number of individuals with metabolic syndrome components blood pressure altered, while more participants in the CF group with LVD had low high-density lipoprotein (HDL) levels. The IF group had more participants with a higher waist-to-hip ratio (WHR). No significant difference was observed between metabolic syndrome, cytokine and adipocytokine level, and clinical forms of the disease or in relation to LVD. Individuals with the IF showed metabolic and immunological profiles compatible with increased disease control, whereas those with CF showed marked inflammatory immune response.